Predictive Factors of Concerns about Falling in People with Parkinson's Disease: A 3-Year Longitudinal Study - Lindh-Rengifo, Magnus (Parkinsons Dis, 2019)
INTRODUCTION: Fear of falling (FOF) is more common in people with Parkinson's disease (PD) than in healthy controls. It can lead to several negative consequences such as restrictions in everyday life. Moreover, FOF is a risk factor for future falls. AIM: This study aimed to identify predictive factors of FOF (conceptualized as concerns about falling) after three years, with and without adjusting for concerns about falling at baseline, in people with PD. METHODS: This study included 151 participants (35% women) with PD. At baseline, their mean (SD) age and PD duration were 68 (±9.0) and 9 (±6.1) years, respectively. The Falls Efficacy Scale-International (FES-I) was used as the dependent variable in multivariable linear regression analyses. RESULTS: The mean (SD) FES-I score increased from 28.1 (11.9) to 33.1 (14.0) three years later (p < 0.001). The strongest (according to the standardized regression coefficient, β) predictor of concerns about falling was walking difficulties (β = 0.378), followed by age (0.227), problems maintaining balance while dual tasking (0.172), and needing help in daily activities (0.171). When adjusting for baseline FES-I scores, the strongest predictive factor was problems maintaining balance while dual tasking (β = 0.161), which was followed by age (0.131) and female sex (0.105). CONCLUSIONS: This study pinpoints several predictive factors of concerns about falling that are modifiable and which could be addressed in rehabilitation: perceived walking difficulties, having problems maintaining balance while dual tasking, and dependence on others in daily activities. The importance of dual tasking is a novel finding, which future studies need to confirm or refute. One should be aware of the fact that an increased age predicts concerns about falling with and without adjusting for baseline FES-I scores, whereas female sex predicts concerns about falling only when adjusting for baseline FES-I scores.